Effects of radiofrequency on adipose tissue: A systematic review with meta-analysis - Vale, Ana Luísa (2020)
Equipment that acts in the reduction in adipose tissue are becomingwidely investigated. One of the resources that begin to gain recognition is radiofre-quency. To verify the existence of scientific evidence and the methodological qualityof the articles on the effects of radiofrequency in the reduction in adipose tissue. Systematic review with meta‐analysis on the effects of radiofre-quency on adipose tissue. The research was carried out using several databases andincluding experimental studies only in humans. The evaluation of the methodologicalquality of the articles was done based on the PEDro Scale. Twelve articles related with adipose tissue and cellulitis were included.There was a great variability of protocols, and the methodological quality was gen-erally low and the methods most used for the evaluation of results were anthro-pometry, photography, and histopathology. Clinical results suggest a positive effectof radiofrequency on the reduction in adipose tissue, proving an increase in adipo-cyte lipolysis. After statistical analysis, it was verified that the anthropometry pre-sented questionable results. The clinical results of the studies point to the positive effects ofradiofrequency on the reduction in adipose tissue; however, the low methodologicalmake this topic still debatable, requiring more controlled studies.